PROBLEMS AND PROSPECTS OF DEVELOPMENT OF RISK MANAGEMENT INNOVATION ACTIVITIES OF COMMERCIAL BANKS - Vladislav Albert (Вестник Северо-Кавказского федерального университета, 2022)
The aim of the article is to identify existing problems and future prospects of improving the risk management of the banking innovation. A wide variety of banking innovation and continuous development of new technology involves the use of not only the existing standards and methods, but also requires an individual approach to each bank. The totality of these ways of assessing and managing the risks of innovation needed for the effective operation of the credit institution. In modern conditions it is necessary continuous improvement of risk management innovation as the development of technology and innovation in credit institutions significantly expand the amount of risk, it is appropriate to modernize and management technologies